First records of Enchytraeidae (Annelida, Clitellata) from the Three Parallel Rivers region - Chen, Jing; Jiang, Wanxiang; Xie, Zhicai (Zootaxa, 2016)
The Three Parallel Rivers region is not only an important World Natural Heritage area but also one of the hotspots of world biodiversity with many endemic organisms. However, little is known about the soil fauna of this region, and nothing about enchytraeids. Here we describe two species from the Laojun Mountain, one of the eight eminent mountain chains in this region, Chamaedrilus cf. ozensis Torii, 2015 and Mesenchytraeus laojunensis sp. nov. The latter belongs to a group of Mesenchytraeus species characterized by spermathecae with one ampullar diverticulum and a communication with the oesophagus, and is thus far the southernmost member of this genus in China. It has two exceptional traits within Mesenchytraeus: a large sperm funnel (more than 2000 µm in length) and a subterminal attachment of the vas deferens to the atrium. In addition, it is distinguished from the other congeners within this group by coelomocytes with distinct refractile vesicles, five pairs of preclitellar nephridia, and the presence of abundant and flame-shaped sperm bundles in sperm sacs, which extend backwards into XVII–XXII.